GAMBARAN KARAKTERISTIK RESPONDEN RHEUMATOID ARTHRITIS PRE TREATMENT GINGER OIL (Zingiber Officinale Rosc) DAN TERAPI RESISTED ACTIVE MOVEMENT - Muliyani Muliyani; Nazhipah Isnani; Enny Fauziah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Rheumatoid arthritis (RA) is the most common autoimmune inflammatory arthritis in adults. Pharmacological treatment is quite effective to overcome it, but in some cases, especially in elderly RA sufferers, pharmacological treatment such as non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids and DMARD (Disease Modifying Antirheumatic Drugs) have an impact on drug side effects, namely gastrointestinal disorders that cause toxic effects on liver and kidney. The developed natural medicine treatment has been supported by several previous studies that provide anti-inflammatory benefits, namely, ginger (Zingiber Officinale Rosc.). Ginger (Zingiber Officinale Rosc.) The method used is descriptive. The purpose of this study was to determine the characteristics of respondents who suffer from rheumathoid arthritic therapy with essential ginger oil and resisted active movement. The results of the study showed that as many as 20 respondents who suffered from rheumatoid arthritis, based on their characteristics, the most were female, namely 16 people (80%, ages 60-75 years, as many as 15 people (75%), the most part of the joints experiencing rheumathoid arthritis. occurred in the knee as many as 9 people (45%), work history, at most not working as many as 8 people (40%), history of injury, there were most injuries as many as 12 people (60%)